2018
DOI: 10.1113/jp276644
|View full text |Cite
|
Sign up to set email alerts
|

Acute hydrocortisone administration reduces cardiovagal baroreflex sensitivity and heart rate variability in young men

Abstract: Key points A surge in cortisol during acute physiological and pathophysiological stress may precipitate ventricular arrhythmia and myocardial infarction.Reduced cardiovagal baroreflex sensitivity and heart rate variability are observed during acute stress and are associated with an increased risk of acute cardiac events.In the present study, healthy young men received either a single iv bolus of saline (placebo) or hydrocortisone, 1 week apart, in accordance with a randomized, placebo‐controlled, cross‐over st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 76 publications
(201 reference statements)
1
10
0
Order By: Relevance
“…These results indicate a possible interaction between the HPA axis and ANS. The link between these two systems was also observed in the study conducted by Adlan et al (13), who reported increases in HR and blood pressure, as well as a reduction in HRV following hydrocortisone administration in healthy young men. HRV measures, time- domain (RMSSD, pNN50), and frequency-domain (high-frequency power (HF) have been negatively associated with higher cortisol total daily output and steeper cortisol diurnal slope in the healthy pediatric population (2).…”
Section: Discussionsupporting
confidence: 65%
“…These results indicate a possible interaction between the HPA axis and ANS. The link between these two systems was also observed in the study conducted by Adlan et al (13), who reported increases in HR and blood pressure, as well as a reduction in HRV following hydrocortisone administration in healthy young men. HRV measures, time- domain (RMSSD, pNN50), and frequency-domain (high-frequency power (HF) have been negatively associated with higher cortisol total daily output and steeper cortisol diurnal slope in the healthy pediatric population (2).…”
Section: Discussionsupporting
confidence: 65%
“…For instance, the IVP‐induced cortisol response could attenuate a second cortisol response and this, in turn, could translate to lower autonomous, neural, and psychological responses. Exogenous administration of steroids has been associated with acute increases in heart rate and decreased heart rate variability (Adlan et al, 2018; Dodt, Keyser, Mölle, Fehm, & Elam, 2000) and changes in neural activity of the hippocampus (Symonds, McKie, Elliott, William Deakin, & Anderson, 2012). While a previous study showed that cortisol increases self‐reported arousal (Abercrombie, Kalin, & Davidson, 2005), there is little evidence for acute cortisol effects on mood (Putman & Roelofs, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Anton [24] have elicited a stress response in clinically healthy cows by intramuscularly administering a single bout of ACTH and measured higher heart rate and lower HF values 30 min after the injection, however, did not address the physiological link between ACTH stimulation and decreased HRV. It is known that the ACTH stimulation test in humans has the temporary side effects of nausea, blushing, or palpitations [58], and there is evidence that a single bout of hydrocortisone reduces baroreflex sensitivity and HRV and increases systolic blood pressure [59]. In rats, a short-lived increase in blood pressure besides unchanged heart rate was observed as a result of ACTH administration [60].…”
Section: Discussionmentioning
confidence: 99%